HUBUNGAN PERSEPSI KECELAKAAAN KERJA DENGAN UNSAFE ACTION PADA PEKERJA KETINGGIAN DI PROYEK PEMBANGUNAN PLTA KERINCI MERANGIN HIDRO JAMBI - Wenny Murdina Asih; Yeni Herlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
One of the things that influences behavior is perception. If workers' perceptions of workplace hazards/risks are low, they are more likely to engage in risky behavior and cause workplace accidents. The goal of this study is to examine if there is a link between worker perception and risky behavior among high-altitude workers working on the Kerinci Merangin Hydroelectric Power Plant development project. A cross sectional research design used in this study, which uses quantitative approaches. From April to August 2021, this study was conducted in the Kerinci Merangin Hydro hydropower project, which has a population of 65 persons. The total sampling approach was selected in this research. SPSS software is used to process the data. According to the data, 58.5 % of workers at heights have a positive perception, whereas 41.5 % have a negative perception. When it comes to the unsafe action variable, 53.8 % of workers at heights are acting safely, while the remaining 46.2 % are acting unsafely. The bivariate test resulted in a p-value of 0.026, indicating that there is a significant relationship between perception and unsafe action.Keywords: Perception, Unsafe Action, and Worker at Height.